The Effect of The Electronic Word of Mouth on Purchase Decision with Image as Intervening Variable - Asti Widyastuti; Marsudi; Luqman Dzul Hilmi (Jurnal Manajemen Bisnis dan Kewirausahaan (JAMANIKA), 2022)
This study aims to determine and analyze the effect of electronic word of mouth on purchase decisions with the brand image as an intervening variable on customers of Scarlett whitening in Shopee. The population in this study was Scarlett consumers who made purchases on the Shopee application. 100 respondents were selected by a purposive sampling method. The data analysis technique in this study uses a scale range and path analysis. The process of data analysis was performed with SPSS 26.0. The result showed that electronic word of mouth had a positive and significant effect on the purchase decision of Scarlett whitening in Shopee. Electronic word of mouth had a positive and significant effect on the brand image of Scarlett whitening. The brand image had a positive and significant effect on the purchase decision of Scarlett whitening in Shopee.